Johor Pakatan may unravel over Gelang Patah seat: DAP-PKR RIVALRY: All eyes on DAP dinner on Monday for hint on who will contest seat - Ariff, Syed Umar (New Straits Times, 2013)
THE bespectacled man sounded jovial on the other end of the line.The sore throat, which he had been suffering from for the past two days, did not stop Dr Boo Cheng Hau from speaking to this writer.